2021
DOI: 10.1021/acs.inorgchem.1c01522
|View full text |Cite
|
Sign up to set email alerts
|

High and Tunable Proton Conduction in Six 3D-Substituted Imidazole Dicarboxylate-Based Lanthanide–Organic Frameworks

Abstract: Six isostructural three-dimensional (3D) Ln(III)−organic frameworks, {[Ln 2 (HMIDC) III (2), Sm III (3), Nd III (4), Pr III (5), and Ce III (6)], have been fabricated by using a multifunctional ligand of 2methyl-1H-imidazole-4,5-dicarboxylic acid (H 3 MIDC). Ln-metal−organic frameworks (MOFs) 1−6 present 3D structures and possess abundant H-bonded networks between imidazole-N atoms and coordinated and free water molecules. All the six Ln-MOFs demonstrate humidity-and temperature-dependent proton conductivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 72 publications
3
26
0
Order By: Relevance
“…Nonetheless, Dy-MOF can still show good proton conductivity. A similar situation can be observed in some other carboxylate-based MOFs …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Nonetheless, Dy-MOF can still show good proton conductivity. A similar situation can be observed in some other carboxylate-based MOFs …”
Section: Resultsmentioning
confidence: 98%
“…Proton conduction is another important proton-related property of MOFs. Proton-conducting materials have attracted extensive attention as solid-state electrolytes for fuel cells. In terms of proton conductors, the highly tunable crystal structure and variously modified pore surfaces of MOFs provide great opportunities to improve proton conduction and provide an ideal crystal model for insight into the mechanism of proton transfer. For most proton conductors, the transport of protons is achieved by the hopping of protons in the hydrogen-bonding network . Zuo et al reported an In-based 2D conductive MOF with a high proton conductivity of 1.30 × 10 –2 S·cm –1 .…”
Section: Introductionmentioning
confidence: 99%
“…The proton conductivity property was measured under different temperatures and variable relative humidity conditions. In general, the proton conductivity (σ) value increases with the temperature or humidity [28,29] …”
Section: Resultsmentioning
confidence: 99%
“…In general, the proton conductivity (σ) value increases with the temperature or humidity. [28,29] The AC impedance spectroscopy of the solid pelletized sample was used to investigate the proton conduction behaviors at various RH and temperatures. We use the pelletized sample to measure proton conductivity with the increase of RH at 30 °C (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
“…Note that as the temperature or humidity increases, the diameter of the semicircle becomes smaller. This phenomenon belongs to the characteristic proton conduction behavior. …”
Section: Resultsmentioning
confidence: 99%